Heurística especializada aplicada na alocação ótima de bancos de capacitores em sistemas de distribuição radial - Vilchez Lazo, Ruben Ernesto [UNESP] (2015)
In this work we proposes a specialized heuristic algorithm for optimal allocation of capacitor banks in radial distribution systems, whose goal is to minimize costs due to energy losses, subject to some operational restrictions of the electric distribution system. To accomplish this goal the following subjects were developed: A constructive heuristic algorithm, which has as primary task the allocation of capacitor banks in buses with the most high-demand for reactive power and also search for an initial solution to minimize energy losses costs and a meta-heuristic which uses variable neighborhood descend search, in which we implemented appropriate neighborhood structures for the allocation problem of capacitor banks in electric system buses. The specialized heuristic uses a new concept for the optimal allocation of capacitor banks to develop a powerful and user-friendly optimization tool for the development of mathematical models for mixed integer nonlinear programming problems. The specialized heuristic was implemented in the programming language Fortran 90 and simulations were performed with radial distribution systems of 33, 70 and 202 buses. The results were compared with other research works that also tested with these electrical systems. Thus, it was verified that the algorithm has a good performance because it generates good quality solutions meeting all the physical and operational constraints of the problem